1984
DOI: 10.1126/science.6729450
|View full text |Cite
|
Sign up to set email alerts
|

T and Tn, General Carcinoma Autoantigens

Abstract: Primary and metastatic carcinomas are epithelial in origin and comprise by far the largest group of malignant tumors in humans. In most of these tumors, T and Tn antigens, whose epitopes have been synthesized, are uncovered and immunoreactive. In all other tissues T and Tn antigens are masked and not accessible to the immune system; they are generally precursors in normal complex carbohydrate chains. Thus, carcinomas have antigens recognized as foreign by the patients' immune system. The expression of T and Tn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
657
0
11

Year Published

1994
1994
2006
2006

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 964 publications
(696 citation statements)
references
References 62 publications
11
657
0
11
Order By: Relevance
“…Several tumor-associated antigens have been identified on mucins (Springer, 1984;Cao et al, 1995;Fukuda, 1996;Baldus et al, 2000;Schneider et al, 2001;Hakomori, 2002). Mucin-type glycoproteins are heavily glycosylated and are mainly decorated with complex O-glycans.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several tumor-associated antigens have been identified on mucins (Springer, 1984;Cao et al, 1995;Fukuda, 1996;Baldus et al, 2000;Schneider et al, 2001;Hakomori, 2002). Mucin-type glycoproteins are heavily glycosylated and are mainly decorated with complex O-glycans.…”
Section: Introductionmentioning
confidence: 99%
“…T antigen (core 1 structure) and its related carbohydrate antigens, such as Tn, T, and their sialylated variants, are oncofetal carbohydrate antigens (Springer, 1984;Cao et al, 1995;Fukuda, 1996;Brockhausen, 1998Brockhausen, , 1999Baldus et al, 2000;Schneider et al, 2001;Hakomori, 2002). Changes in the expression of T antigen-related carbohydrates on cell surfaces have been observed in a variety of cancers (Hanisch and Baldus, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Changes in surface membrane glycoproteins are common phenomena in cancer cells (Springer, 1984). Itzkowitz et al (1989Itzkowitz et al ( , 1990 reported that the rate of expression of STN is low in normal colon mucosa, and that expression of STN is an independent prognostic factor for colon cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…La exposición del antígeno Tn en eritrocitos ocasiona el síndrome Tn, o síndrome de poliaglutinabilidad, que es un trastorno caracterizado por la presencia de residuos de N-acetilgalactosamina (GalNAc) en la superficie de la célula roja que, normalmente, se encuentran enmascarados y unidos a Ser/Thr en las sialoglicoproteínas de membrana (17,18). Los antígenos T y Tn también se han encontrado asociados a carcinomas, expuestos en la membrana externa de células tumorales comunes y en metástasis (19,20); la proporción relativa de estos antígenos en las células está estrechamente relacionada con la agresividad con la que evoluciona el tejido canceroso (20).…”
unclassified